Desain Elektrolisa Air Sebagai Bahan Bakar Kompor Gas - Jefri Lianda; Eko Cahyo; Putra Hakiki; Rodiah Rodiah (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
The useof fuel oil and LPG gasare often constrained and often disconnected and the price is expensive.This study makesa gas stove with fuel water through electrolysis system. The process of water electrolysis to separate water molecules into hydrogen and oxygen gasby means ofan electric currentto the electrolyte (a solution of water anda catalyst NaCl) through the aluminum electrode. The results achieved in the form of gasfrom the electrolysis has can be used to turn on the gas stove with an electric curren to f 0.52 amperesKeywords: electrolysis, electric, gas, water, NaCl